Morphology of complexes formed between β‐lactoglobulin nanofibrils and pectins is influenced by the pH and structural characteristics of the pectins. Issue 11 (November 2016) - Hettiarachchi, Charith A.; Melton, Laurence D.; Williams, Martin A. K.; McGillivray, Duncan J.; Gerrard, Juliet A.; Loveday, Simon M.
Abstract: For the optimal use of β ‐lactoglobulin nanofibrils as a raw material in biological composites an in‐depth knowledge of their interactions with other constituents is necessary. To understand the effect of electrostatic interactions on the morphology of resulting complexes, β ‐lactoglobulin nanofibrils were allowed to interact with pectins in which the amount of available negative charge was controlled by selecting their degree of methylesterification. In this study, citrus pectins having different degrees of methylesterification (∼48, 67, 86, and 97%) were selected and interacted with nanofibrils at pH 2 and pH 3, where they possess a net positive charge. Electrostatic complexes formed between β ‐lactoglobulin nanofibrils and all pectin types, except for the sample having a degree of methylesterification of 97%. The morphology of these complexes, however, differed significantly with the degree of methylesterification of the pectin, its concentration, and the pH of the medium, revealing that distinct desired biological architectures can be attained relatively easily through manipulating the electrostatic interactions. Interestingly, the pectin with a degree of methylesterification of 86% was found to crosslink the β ‐lactoglobulin nanofibrils into ordered 'nanotapes'.